Monthly fuel usage of the generator sets and boilers at Australian Antarctic Stations - BONNICE, JEREMY (hasPrincipalInvestigator); RATCLIFFE, GUY (processor); SHEERS, ROBERT (processor); Australian Antarctic Data Centre (publisher)
INDICATOR DEFINITION The quantity of fuel used by generator sets and boilers at Casey, Davis, Mawson and Macquarie Island stations as measured on a monthly basis and reported in the monthly reports from the Station Plant Inspectors to the Kingston (Head Office) Mechanical Supervisor. TYPE OF INDICATOR There are three types of indicators used in this report: 1.Describes the CONDITION of important elements of a system; 2.Show the extent of the major PRESSURES exerted on a system; 3.Determine RESPONSES to either condition or changes in the condition of a system. This indicator is one of: PRESSURE RATIONALE FOR INDICATOR SELECTION The amount of fuel used in Antarctica for power generation and heating is proportional to environmental impact due to the emissions released. Special Antarctic Blend (SAB), a light diesel like fuel, is used at the stations to power the station generator sets, to provide heat through boilers, and to run plant and equipment including the station incinerator and vehicles. DESIGN AND STRATEGY FOR INDICATOR MONITORING PROGRAM Spatial scale: Australian Antarctic stations: Casey (lat 66 deg 16' 54.5& S, long 110 deg 31' 39.4& E), Davis (lat 68 deg 34' 35.8& S, long 77 deg 58' 02.6& E), Mawson (lat 67 deg 36' 09.7& S, long 62 deg 52' 25.7& E) and Macquarie Island (lat 54 deg 37' 59.9& S, long 158 deg 52' 59.9& E). Frequency: Monthly reports Measurement technique: The figures are obtained by direct reading of gauges on the stations on a regular basis. The data are recorded in the Plant Inspectors monthly reports. RESEARCH ISSUES In the future, it is planned to automate the collection of most of this data. LINKS TO OTHER INDICATORS SOE Indicator 1 - Monthly mean air temperatures at Australian Antarctic stations. SOE Indicator 2 - Highest monthly air temperatures at Australian Antarctic Stations SOE Indicator 3 - Lowest monthly air temperatures at Australian Antarctic Stations SOE Indicator 4 - Monthly mean lower stratospheric temperatures above Australian Antarctic Stations SOE Indicator 7 - Monthly mean of three-hourly wind speeds (m/s) SOE Indicator 48 - Station and ship person days SOE Indicator 57 - Monthly total of fuel used by station incinerators SOE Indicator 58 - Monthly total of fuel used by station vehicles SOE Indicator 59 - Monthly electricity usage SOE Indicator 60 - Total helicopter hours SOE Indicator 61 - Total potable water consumption SOE Indicator 65 - Station footprint for Australian Antarctic stations